The Effect of Temperature Variation and Absorber Type on the Pyrolysis of Sawdust Using Microwaves - Muhammad Arief Saputro; Harwin Saptoadi; Robertus Dhimas Dhewangga Putra (Institute for Research and Community Service (LPPM), Universitas Malikussaleh, Indonesia, 2025)
Biomass is a renewable and environmentally friendly energy source. However, its utilization is often inefficient, such as in direct combustion and biological processes. Pyrolysis, a method of heating biomass without oxygen, can enhance the value of biomass by producing gas, oil, and char. Microwave technology makes the pyrolysis process more efficient. This study varied the pyrolysis temperatures (350°C, 400°C, 450°C, 500°C) and used KOH and SiC as varied absorbers. KOH was chosen because it contains O and H elements that help absorb microwaves, while SiC is effective in improving heating efficiency. The results showed that pyrolysis at 350°C produced the highest biochar yield of 59.3% of the biomass weight. The highest bio-oil yield, 27.7%, was obtained at 400°C.Pyrolysis without an absorber demonstrated that sawdust cannot absorb microwaves effectively, as the temperature only reached around 200°C, which is insufficient for pyrolysis. SiC increased the temperature of the sawdust (between 200°C - 330°C) earlier than KOH. However, KOH led to higher bio-oil production than SiC. The findings suggest that absorber type and pyrolysis temperature significantly influence the efficiency and product distribution. Microwave-assisted pyrolysis with absorbers offers a promising method for converting biomass into valuable energy products, highlighting its potential for further development.